MITgcm model setup and output for "Impact of subglacial freshwater discharge on Pine Island Ice Shelf" - Yoshihiro Nakayama (Zenodo, 2021)
Here, it contains the results of the regional PIGsimulation. Model grid is lat-lon similar to Nakayama et al., 2019 roughly 200 m in the region. See Nakayama et al., submitted to GRL for detail. For complete model output (10*Qsg and 50*Qsg cases), please access NASA data (Registration is required). https://ecco.jpl.nasa.gov/drive/files/ECCO2/High_res_PIG/PIG_only_200m Contents can be downloaded easily using wget (see link below). https://ecco-group.org/docs/wget_download_multiple_files_and_directories.pdf (Contents) code.zip(code to run thissimulation) input.zip(input file required for this simulation) latlon_run23.zip (CTRL) latlon_run24.zip (Qsg case) latlon_run25.zip (2*Qsg case) (How to build and run) mkdir build ./././tools/genmake2 -of ./././tools/build_options/linux_amd64_ifort+mpi_ice_nas -mpi -mods ./code/ make depend make -j 16 cd . mkdir test cd test ln -sf ./input/* . ln -sf /nobackup/hzhang1/forcing/era_xx_it50/ . cp ./build/mitgcm_uv . qsub latlon_run23.sh